2020
DOI: 10.1038/s41598-020-58971-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual effects of fast and automatic visual ensemble statistics from faces in individuals with typical development and autism spectrum conditions

Abstract: We investigated whether covert ensembles of high-(emotion), and low-level (brightness) visual information, extracted from peripheral faces (presentation/encoding:200 ms), unintentionally influences perception of a central target face stimulus in individuals typically developing (TD) and with autism spectrum condition (ASC). Graded alterations in the summary intensities of the emotion and brightness of the peripheral stimuli modulated the perceptions of the target face in both TD and ASC. In contrast, when we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
3
3
0
Order By: Relevance
“…In contrast, inferior visual processing have also been demonstrated like impaired object boundary detection (Vandenbroucke et al., 2008), inferior contrast detection with static and moving stimuli (Sanchez‐Marin & Padilla‐Medina, 2008), decreased sensitivity to global motion coherence (Spencer et al., 2000) and recognition of biological motion (Annaz et al., 2010; Blake et al., 2003). These studies agree with the notion that lower‐level visual processing are generally superior in ASD individuals relative to higher‐level, for example, human biological motion perception (Dakin & Frith, 2005) and ensemble perception of facial emotions (Chakrabarty & Wada, 2020).…”
Section: Introductionsupporting
confidence: 86%
“…In contrast, inferior visual processing have also been demonstrated like impaired object boundary detection (Vandenbroucke et al., 2008), inferior contrast detection with static and moving stimuli (Sanchez‐Marin & Padilla‐Medina, 2008), decreased sensitivity to global motion coherence (Spencer et al., 2000) and recognition of biological motion (Annaz et al., 2010; Blake et al., 2003). These studies agree with the notion that lower‐level visual processing are generally superior in ASD individuals relative to higher‐level, for example, human biological motion perception (Dakin & Frith, 2005) and ensemble perception of facial emotions (Chakrabarty & Wada, 2020).…”
Section: Introductionsupporting
confidence: 86%
“…In contrast, inferior visual processing have also been demonstrated like impaired object-boundary detection (Vandenbroucke et al, 2008), inferior contrast detection with static and moving stimuli (Sanchez-Marin & Padilla-Medina, 2008), decreased sensitivity to global motion coherence (Spencer et al, 2000) and recognition of biological motion (Annaz et al, 2010; Blake et al, 2003). These studies agree with the notion that lower-level visual processing are generally superior in ASD individuals relative to higher-level, for example human biological motion perception (Dakin & Frith, 2005) and ensemble perception of facial emotions (Chakrabarty & Wada, 2020).…”
Section: Introductionsupporting
confidence: 88%
“…For example, Rhodes et al [31] reported diminished facial ensemble perception in individuals with ASD; however, Karaminis et al [32] did not observe such an effect. More recently, Chakrabarty & Wada [33] reported that peripheral face ensembles unconsciously affect the judgement of a facial emotion of a central target, both in participants with typical development and autism spectrum condition. They also observed large individual differences in spatial facial ensembles, especially when individuals intentionally recognized the averaged emotion of five faces.…”
Section: Introductionmentioning
confidence: 99%